New times in New Zealand? : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Sociology at Massey University - Edmonds, Philip Ferguson (Massey University, 1996)
There is widespread agreement that New Zealand, among other advanced nations, has experienced major economic, political and cultural change in recent times. Yet the causes, the extent and the implications of these changes are still very much contested. The 'New Times' thesis has offered one interpretation of change which suggests a transformational shift has occurred following the 'breakdown' of the 'postwar settlement'. This breakdown is seen as a result of the declining influence of structural forces where the effect has been the emergence of a society characterised by diversity and difference. In this thesis, I critically assess the New Times position, and in doing so, contemplate its ability to help clarify and define more precisely the meaning of New Zealand's recent change. I conclude that while the New Times project is ultimately ineffectual in providing a sound theoretical and empirical account of contemporary developments, it does usefully highlight the need, particularly in New Zealand, for a new approach to account for changing social formations.
Keywords: Economic conditions, New Zealand; Economic policy, New Zealand; Politics and government, New Zealand